2013
DOI: 10.4236/jcdsa.2013.32025
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Block Staining of Human Hair Shafts and Insect Cuticles by Ammonium Thioglycolate to Enhance Transmission Electron Microscopic Observations

Abstract: We have developed a method where, after glutaraldehyde fixation, human hair shafts and insect cuticles are treated with ammonium thioglycolate (ATG) to improve ultrastructural staining. Conventional transmission electron microscopic (TEM) preparations do not distinguish the A-layer and the exocuticles of hair shafts. However, after ATG treatment, the A-layer appears in higher contrast. ATG treatment has also been used to observe the fibrillar structure in the cortex. In the cuticle of beetles, the epicuticle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Within the cortex region we find disk-shaped areas of about 300 nm diameter, where the infrared absorption is reduced (that is, the protein content is reduced). Their size and distribution corresponds to that of melanin granules observed in electron microscopy images 53 . However, we found that nano-FTIR spectra of the individual granules can differ significantly from each other.…”
Section: Resultssupporting
confidence: 64%
“…Within the cortex region we find disk-shaped areas of about 300 nm diameter, where the infrared absorption is reduced (that is, the protein content is reduced). Their size and distribution corresponds to that of melanin granules observed in electron microscopy images 53 . However, we found that nano-FTIR spectra of the individual granules can differ significantly from each other.…”
Section: Resultssupporting
confidence: 64%
“…All samples had well defined endocuticle and exocuticle. Additionally, gray-control (G-Control), black AA (B-AA) and white AA (W-AA) samples presented an intact A-layer with a higher electron density than the endo-and exocuticle (Popescu & Höcker, 2007;Bhushan, 2008;Sato et al, 2013). Noticeably, AA samples, and particularly W-AA ( (Tobin, Fenton & Kendall, 1990a, 1990bTobin et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Hair concentrations of heavy metals like arsenic, lead, cadmium and mercury, were correlated with their presence in the internal organs, blood and urine (Robbins, 2012). TEM is an essential tool to assess the homogeneity of a sample and study biological systems at near-atomic-level resolution (Wagner et al, 2007;Sato et al, 2013;Kinsler et al, 2013;Smentkowski, 2014). SAXS is a powerful method providing detailed micro-to nanoscale structural and physical information (the specific inner surface, surface to volume ratio, or lattice type and dimensions) for a variety of systems (Schnablegger & Singh, 2013).…”
mentioning
confidence: 99%
“…Therefore, we tested thicknesses of the abdominal cuticles of psyllids to analyze the differences in intractability of the two morphotypes. Cuticle thickness measurement was performed according to the definition described in previous studies: that arthropod cuticle is composed of two layers, the outer protein-rich epicuticle and the procuticle (including exocuticle and endocuticle), which presents as a lamellar base structure based upon electron micrographs [50,51].…”
Section: Methodsmentioning
confidence: 99%